Formulation and evaluation of herbal valhas hair oil - S.SRINIVASAN (International Journal of Pharma and Bio Sciences, 2019)
Ayurvedic experts claim that in the region of 50% of Indian women and men are losing hair faster. The current beauty industry has damaged hair care to be precise. With generic formulations, thinned & inferior herbs, Ayurvedic hair oils that otherwise seem hopeful have failed to reach expectations. Even though natural sciences are considered beneficial, it has scarcely shown any results. In recent years hair oil commonly used by the common peoples to promote hair growth without side effects has become the need of the hour. Our objective of the study is to formulate and evaluate valhas oil and compared with marketed hair oils. The present work was aimed and focused on to formulate herbal oil for general purpose (application in hairs) and the ingredients to be used using various herbs. The different types of various herbal hair oil were used to compared with our new product (Velhas) The formulated herbal oil was evaluated and various parameters were determined and are reported in this paper. Our product gave the better result compared to other recent market product with best effect in hair growth.